Long non-coding RNA DILC regulates liver cancer stem cells via IL-6/STAT3 axis - Wang, Xue; Sun, Wen; Shen, Weifeng; Xia, Mingyang; Chen, Cheng; Xiang, Daimin; Ning, Beifang; Cui, Xiuliang; Li, Hengyu; Li, Xiaofeng; Ding, Jin; Wang, Hongyang (Journal of hepatology, 2016)
[Display omitted] Emerging evidence has demonstrated the aberrant expression of long non-coding RNAs (lncRNAs) in various malignancies including HCC. However, the knowledge of cancer stem cell-related lncRNAs remains limited. lnc-DILC (lncRNA downregulated in liver cancer stem cells (LCSCs)) was identified by microarray and validated by real-time PCR. The role of lnc-DILC in LCSCs was assessed both in vitro and in vivo. Pull down assay and oligoribonucleotides or oligodeoxynucleotides treatment were conducted to evaluate the interaction between lnc-DILC and interleukin-6 (IL-6) promoter. Depletion of lnc-DILC markedly enhanced LCSC expansion and facilitated HCC initiation and progression, whereas ectopic expression of lnc-DILC dramatically inhibited LCSC expansion. Mechanistically, lnc-DILC inhibited the autocrine IL-6/STAT3 signaling. The putative binding locus of lnc-DILC within IL-6 promoter was confirmed by pull down assay. Consistently, the oligoribonucleotide mimics and an oligodeoxynucleotide decoy of lnc-DILC abrogated the effects on IL-6 transcription, STAT3 activation and LCSC expansion triggered by lnc-DILC depletion and lnc-DILC overexpression. Moreover, our data suggested that lnc-DILC mediated the crosstalk between TNF-α/NF-κB signaling and IL-6/STAT3 cascade. Clinical investigation demonstrated the reduction of lnc-DILC in patient HCCs, and suggested the correlation between lnc-DILC levels and IL-6, EpCAM or CD24 expression. Decreased lnc-DILC expression in HCCs predicts early recurrence and short survival of patients, highlighting its prognostic value. lnc-DILC mediates the crosstalk between TNF-α/NF-κB signaling and autocrine IL-6/STAT3 cascade and connects hepatic inflammation with LCSC expansion, suggesting that lnc-DILC could be not only a potential prognostic biomarker, but also a possible therapeutic target against LCSCs.